Islamic Dimensions of the East Asian Economic Miracle (American Journal of Islam and Society, 1999)
In PerspectiveThis editorial seeks to identify the missing dimensions of Islamic economicsand the Islamic dimensions of East Asian economies. In doing so,it advances a critical review of the present discourse on Islamic economicsand highlights some of its oversights. At the outset, it must be clearlyunderstood that I am not critical of the very idea of an Islamic economics.I think that at a time when global intellectual leadership has been usurpedby those who consciously subvert the idea of the divine and the role ofdivine mandates in the organization and governance of human affairs,Islamic economics, like Islamic philosophy and Islamic social sciences, hassucceeded in at least presenting a paradigmatic alternative that still maintainesthe centrality of transcendence in human existence.While I am all for sustaining the resistance to secularization of all knowledges,I am critical of the current discourse on Islamic economics becauseof its disconnection between theory and practice and because, for reasonsthat have not been explored systematically but are intuitively discernable,it has made Islamic economics synonymous with' interest-free banking.Many important elements of Islamic economics are completely ignored oreven suppressed. Perhaps this may be a reason why Islamic economieshave not really materialized. The importance of these less studied principlescan be discerned by studying how they have played a cardinal role inthe world's fastest growing region, East Asia. I intend to show how EastAsian economies have institutionalized Islamic principles in their contemporaryeconomic practices and are harvesting great benefits. It is ironic that ...